Nominations of the Stavropol poreyurbanonyms - I. V. Zhelyabova; G. O. Ilagaeva (Гуманитарные и юридические исследования)
The article is devoted to the study of the onomastic space of the city of Stavropol. The official and unofficial names of the Stavropol stops (poreyurbanims) are analyzed in synchronic and diachronic aspects, the peculiarities of the existence of urbanonyms in the modern linguistic picture of the world of townspeople are indicated.  Poreyurbanonyms, in our opinion, are of great importance in the toponymic system of any city. They are a source of information about the organization of the city, its structure (they call educational, cultural, medical and commercial institutions, streets, squares, etc.), and they help the guests of the city find their way.  However, often in the speech of residents, the old names of stopping points remain, since they were significant places for the townspeople and remained in the memory of residents of venerable age.  In addition, there are jargonized nominations of periurbanonyms, which are familiar to drivers and local residents and confuse visitors to the city.The study describes trends in the development and existence of names, which depend on socio-cultural, economic and political situations.  In our opinion, this work will provide an opportunity to feel the power and richness of the Russian language, the Russian regional language.Emphasis is placed on the low degree of knowledge of onyms of different species in the Stavropol Territory and the North Caucasus.  These studies will be able to expand knowledge in the field of regional onomastics, as well as in the field of such a new scientific direction as urban studies, which deals with the study of urban realities and is interdisciplinary in nature, based on data from history, geography, linguistics.Onomasticon in Stavropol is unstable, constantly changing, new models appear and old models fade, therefore, over time, the unofficial names of stops are replaced by official ones and are fixed in the speech culture.